RECREATIONAL AND FUNCTIONAL ZONING OF TERRITORIES WITH TECHNOGENIC IMPACT FOR THE PURPOSE OF SUSTAINABLE DEVELOPMENT OF THE REGION - Zharas G. BERDENOV; Aigul YEGINBAYEVA; Nurlybek ZINABDIN; Aidana BEKETOVA; Gulshara MENDYBAYEVA; Aizhan ASSYLBEKOVA; Hakan ÖNAL (Geo Journal of Tourism and Geosites)
The article delves into the development of a comprehensive concept for the sustainable development of regions characterized by intensive environmental management. This concept is rooted in the interplay of several key factors, including the environmental component, social attractiveness, and infrastructural accessibility. By meticulously analyzing these factors and juxtaposing them with the geographical distribution of recreational facilities, the authors propose the innovative concept of a recreational and functional zone. This concept aims to harmonize environmental, economic, and social considerations to foster sustainable development. In this study, particular attention is given to three districts within the steppe zone of the Aktobe region, which are notable for their high levels of economic development and intensive environmental management practices. The analysis encompasses a thorough examination of the ecological, economic, and sociological dimensions of these areas. The authors explore the intricate dynamics between these components to understand the challenges and opportunities they present for sustainable regional development. Building on this analysis, the article offers specific recommendations and strategies designed to optimize environmental management practices. These recommendations are not only aimed at mitigating potential environmental impacts but also at enhancing the development of recreational areas as a pivotal element of the region's sustainable development strategy. The authors argue that such an approach is crucial for ensuring the long-term viability and resilience of the region, balancing economic growth with the preservation of its natural and social environments.